2006
DOI: 10.1007/s10458-005-6104-4
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating Self-interested Planning Agents

Abstract: We consider planning problems where a number of non-cooperative agents have to work on a joint problem. Such problems consist in completing a set of interdependent, hierarchically ordered tasks. Each agent is assigned a subset of tasks to perform for which it has to construct a plan. Since the agents are non-cooperative, they insist on planning independently and do not want to revise their individual plans when the joint plan has to be assembled from the individual plans. We present a general formal framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Agent A 2 can process tasks t 3 in the interval [4,7] while starting t 4 in [2,2]. Similarly, agent A 3 can process task t 5 in the interval [8,10] with task t 6 starting in the interval [7,7] and task t 7 in [9,9]. Notice here that any schedule produced by the agents such that these intervals are honored will always lead to a global makespan of 11.…”
Section: Each Such Interval [Lb(t) Ub(t)] ∈ C I With Lb(t) Ub(t) ∈ mentioning
confidence: 99%
See 2 more Smart Citations
“…Agent A 2 can process tasks t 3 in the interval [4,7] while starting t 4 in [2,2]. Similarly, agent A 3 can process task t 5 in the interval [8,10] with task t 6 starting in the interval [7,7] and task t 7 in [9,9]. Notice here that any schedule produced by the agents such that these intervals are honored will always lead to a global makespan of 11.…”
Section: Each Such Interval [Lb(t) Ub(t)] ∈ C I With Lb(t) Ub(t) ∈ mentioning
confidence: 99%
“…Such protocols require simple forms of problem-specific information exchange before the agents can start planning, and they guarantee that if the agents adhere to the protocol, then the individual plans can easily be assembled into a joint plan for the overall task. Examples of such coordination by design strategies are the Temporal Decoupling Method by Hunsberger [27,28] and the pre-planning coordination method discussed in [10]. In these methods, additional constraints are imposed on a set of tasks given to a collection of agents to ensure that they can plan autonomously, while still ensuring that the plan of every agent will satisfy the original set of constraints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [14], it was shown that every fixed task instance can be transformed into a coordinated one by adding a minimum number of intra-agent constraints ∆ = n i=1 ∆ i such that the resulting instance ({T i } n i=1 , ≺ ∪ ∆), is a coordinated instance. In Figure 2, the reader might check that ∆ = {t 7 ≺ t 2 , t 6 ≺ t 3 , t 5 ≺ t 4 } is such a set of additional constraints that turns the fixed task instance into a coordinated one.…”
Section: Plan Coordinationmentioning
confidence: 99%
“…We study three variants of the plan-coordination problem and some factors that influence their complexity. Some results have been published in [14]; the results about the complexity of coordination when the number of agents is kept fixed are new.…”
Section: The Computational Complexity Of Coordinationmentioning
confidence: 99%